(untitled) (Baltic Journal of Sport and Health Sciences, 2021)
Background. Literature suggests cardiorespiratory fitness as a factor influencing cognitive improvement. The authors of the present study sought to investigate if cardiorespiratory fitness related to cognitive performance after an acute bout of game-based exercise of different intensities in adolescents. Methods. As many as 37 adolescents (24 girls and 13 boys, 15–16 years of age) were assigned to three groups: experimental group 1 (EX 1), experimental group 2 (EX 2), and control (CON) group. The experimental groups experienced different levels of exercise intensity (EX 1 – light intensity, EX 2 – vigorous intensity). The Shuttle Run Test was performed a week before the intervention and VO2peak was calculated. Symbol Digit Modalities Test (SDMT) was evaluated before and after the acute intervention. A 2 x 3 repeated-measures ANOVA was used to analyze the SDMT and Pearson’s correlation coefficient was used to estimate the relationship between the cognitive performance (SDMT) and cardiorespiratory fitness (VO2peak). Results. Comparing the SDMT scores before and after the intervention, there were no differences found between the three groups. Neither in any of the experimental groups nor in the control group was a relationship between the SDMT score and VO2peak observed. Conclusion. Acute game-based exercise intervention did not prove to improve cognitive performance effectively. The authors of the present paper did not confirm the relationship between cardiorespiratory fitness and cognitive performance in adolescents. Keywords: exercise, cognitive performance, cardiorespiratory fitness.